The story of maryam - Khan,saniyasnain (china goodwordbooks, 2021)
The Story of Maryam" is a beautifully crafted board book that shows the remarkable story of Maryam (AS), the mother of Prophet Isa (AS), as mentioned in the Quran. This story teaches children about the importance of faith, obedience, and the miraculous birth of Prophet Isa.